Symbolism and Islamic Values in Students’ Reog Stage at Muharam Celebration - Muslih Aris Handayani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Signs, symbols, and meanings are important elements in human interaction. This research aims to reveal how the signs, symbols, and meanings related and can be used to describe the relationship among students in Reog culture staging. The results of the study showed that interaction between muslim’s players on the Reog stage forms togetherness, soul sacrifice, struggle, and friendship. This research of signs, symbols, and meanings in the relationship among Islamic students in Reog staging can be obtained that communication is the process of tagging and signification on signs to obtain a mutual understanding of meaning that involves human creativity in the production, exchange, and meaning process of the signs and symbols. The islamic values of students in Reog Muharam stage are leadership, togetherness, mutual respect and the means of silaturrahmi of muslim’s community in Ponorogo.